Tissue refractometry using Hilbert phase microscopy - Lue, Niyom; Bewersdorf, Joerg; Lessard, Mark D; Badizadegan, Kamran; Dasari, Ramachandra R; Feld, Michael S; Popescu, Gabriel (Optics letters, 2007)
We present, for the first time to our knowledge, quantitative phase images associated with unstained 5 mum thick tissue slices of mouse brain, spleen, and liver. The refractive properties of the tissue are retrieved in terms of the average refractive index and its spatial variation. We find that the average refractive index varies significantly with tissue type, such that the brain is characterized by the lowest value and the liver by the highest. The spatial power spectra of the phase images reveal power law behavior with different exponents for each tissue type. This approach opens a new possibility for stain-free characterization of tissues, where the diagnostic power is provided by the intrinsic refractive properties of the biological structure. We present results obtained for liver tissue affected by a lysosomal storage disease and show that our technique can quantify structural changes during this disease development.